2017
DOI: 10.1016/j.apsusc.2017.02.082
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of r-GO/SiC nano-composites on Magnesium and its Corrosion Behavior in Aqueous Electrolyte

Abstract: Highlights for review  Reduced graphene oxide (r-GO) was synthesized using modified hummer method.  Reduced graphene oxide (r-GO)/Silicon Carbide (SiC) composite were coated on Mg Strip using electro deposition.  Nanocomposite were characterized using Physio-chemical method.  Surface morphology of coated composites was analyzed using SEM/EDAX.  Corrosion study was carried out on the uncoated and coated Mg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(6 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Recent studies revealed that addition of glass fibre up to 30 wt.% exhibits better mechanical strength, hence 30% of glass fibre was kept constant to developed novel composite. Graphene oxide was synthesis by modified hummer's method [25]. Abutilon indicium leaf extract was used to reduce the graphene oxide to avoid the usage of harmful chemicals such as hydrazine hydride, which cause several health issues.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies revealed that addition of glass fibre up to 30 wt.% exhibits better mechanical strength, hence 30% of glass fibre was kept constant to developed novel composite. Graphene oxide was synthesis by modified hummer's method [25]. Abutilon indicium leaf extract was used to reduce the graphene oxide to avoid the usage of harmful chemicals such as hydrazine hydride, which cause several health issues.…”
Section: Methodsmentioning
confidence: 99%
“…The peak arises near 2854 cm −1 is related to C-H stretching vibration. These hydroxyl groups might absorb water molecules and phenolic functional group from the carboxylic group of green extract [25]. C=O stretching vibration of carboxyl groups was detected at 1672 cm −1 .The presence of carboxylic group help in increasing the interaction between the polymer materials that helps in better adhesion.…”
Section: Confirmation Test For Bio-reduced Graphene Oxidementioning
confidence: 99%
“…Magnesium (Mg) and its alloys holds various outstanding properties, such as low density, high thermal conductivity, high damping resistance and better shielding characteristics [1], these properties make Mg as a prime material in various fields of application such as automobile, workstation parts, aerospace components and mobile phones [2][3]. However, Mg and its alloys are highly chemical reactive and likely to agonize severe corrosion in almost all industrial environments during service, that extremely limits their possible application in industrial practice [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Surface modification can effectively enhance the corrosion performance of Mg alloy and, at the same time, can impart different biological properties to the surface. 12−14 Different surface modification methods such as electrodeposition, 15 microarc oxidation (MAO), 16 ion implantation, 17 anodized oxidation, 18 chemical conversion coating, 19 and polymer coating 20 have been widely used. Among these methods, chemical conversion coating, especially Ca−P conversion coating, is one of the most widely used and effective methods, which can simultaneously enhance the biocompatibility and corrosion resistance of Mg alloys.…”
Section: Introductionmentioning
confidence: 99%